Bible. ([S.l.])
1 online resource
Keywords: The Paris Psalter and the Meters of Boethius (1932) contains the texts and comprehensive notes on the Paris Psalter (the most extensive collection of Anglo-Saxon metrical translations of the Psalms) and the Meters of Boethius (the surviving Anglo-Saxon versions of De Consolatione Philosophiae of Boethius.